Payung-payung Cendawan Enterprise - Bakri, Suriana; Beddu, Amiruddin; Solaiman, Roslovelexon; Abdul Die, Ahmad Redzuan; Ahmad, Mohammad Hibatullah (2012)
Payung-payung Cendawan Enterprise is to be established on September 2013. This company is established purposely to make agricultural field as a main source of income in Malaysia. The project will take place on 2 acres land in Kg Bundu Tuhan, Ranau Sabah where the land is owned by one of our business partner. For business starting, we will plant 45000 bags of the shiitake mushrooms and we are planned to increase our production in the future. We are selecting this business because shiitake mushrooms has a high potential to become one of the main exported product and very suitable to be exported as this mushrooms can be dried. Other than that, there is a high demand as many people like to consume it as their additional cooking ingredients such as vegetable. However, many people still do not know that shiitake mushrooms are also have medicinal properties. In addition, it is also can produce other product such as medicinal product, healthy product and many other products. Besides that, nowadays agriculture is driven by new technology that will facilitate works previously done manually. Technology improvement can also shorten growing time for Shiitake mushrooms and also increase the production.